Developing Reproductive Health Communication in Early Marriage (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2020)
Adolescent fertility is an important health and social problem because it is related to the level of morbidity and mortality of mothers and children. The results of the 2017 IDHS show that 7% of women aged 15-19 are already mothers, 5% have given birth, and 2% are pregnant with their first child. The data shows that adolescents are already sexually active, but still have an understanding of low reproductive health. The purpose of this study was to determine the effectiveness of community-based health communication models that developed to improve access to information and public knowledge related to contraceptive methods in young married couples in Rembang Regency in 2019. This researchÂ used Research and Development design with a quasi-experimental data collection method. The population in this study were adolescents who married at a young age in Rembang District, while the sample was adolescents who married young in Sedan and Kragan villages (intervention group), Menoro and Ngasinan (control group). Quantitative data analysis uses univariate, bivariate, and multivariate, while for qualitative data use grounded theory. The effectiveness test showed significant data for knowledge (p = 0,000), attitudes (p = 0.003), access to information (0.012), preferences (p = 0.001), and access to contraception (p = 0,000). It can be concluded that the community-based health communication model can improve knowledge, attitudes, access to information, preferences, and access related to contraception in early married couples